Solution Estimation of Logistic Growth Model with Ensemble Kalman Filter Method - Vianda Nuning Fitriani; Kosala Dwidja Purnomo (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2013)
Ensemble Kalman Filter (EnKF) can be applied for linear or nonlinear models. This paper is aimed to estimate the logistic growth of population models using EnKF. The estimation will be compared with the analytical solution. We assume that we can find the analytical solution of the models. The models is in the specific form i.e comparison between the population growth rate and the amount of population is in the parabolic form. The good estimation will be attained by choosing 100 as size of ensembles in EnKF. The result of estimation really so closed to the analytical solution. Keywords : Analytical solution, EnKF, ensemble